Development of Interactive E-Modules as a Learning Media to Train Visual-Spatial Intelligence on Intermolecular Force Materials - Aulia Pratamadita; Kusumawati Dwiningsih (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This research aims to determine the feasibility of the interactive e-module from its validity, effectiveness, and practicality as a learning media for high school students to train visual-spatial intelligence on intermolecular forces materials. The type of this research is Research and Development (R&D) with the ADDIE development model. There are five (5) stages at the ADDIE model, namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The instruments used in the interactive e-module validation process were content and construct validation sheets, pretest and posttest sheets for effectiveness, and student response questionnaires for its practicality. This researchs’ data were analyzed descriptively quantitatively. The results of the interactive e-module validation obtained a percentage of 90.0% for content validation and a percentage of 90.5% for construct validation, both of which belonged to the very valid category. The effectiveness of the interactive e-module also met the classical completeness criteria, which is 80.0% in the intermolecular force material and 85.0% in the visual-spatial. The T-test results also showed a significant difference between the average pretest and posttest indicated by the sig. 2-tailed value of 0.00 < 0.05 both in terms of intermolecular forces and visual-spatial. In addition, interactive e-modules were also said to be practical to use based on student responses which showed a score of 100% on the content aspect, 99.2% on the linguistic aspect, 97.1% on the usability aspect, and 100% on the presentation aspect. All of them were in the “Very good” category. From these results, it can be concluded that the interactive e-module to train students' visual-spatial intelligence on the material of intermolecular forces is feasible to use in terms of validity, effectiveness, and practicality.